Inflammatory biomarkers and cancer: CRP and suPAR as markers of incident cancer in patients with serious nonspecific symptoms and signs of cancer. Issue 1 (24th April 2017) - Rasmussen, Line Jee Hartmann; Schultz, Martin; Gaardsting, Anne; Ladelund, Steen; Garred, Peter; Iversen, Kasper; Eugen‐Olsen, Jesper; Helms, Morten; David, Kim Peter; Kjær, Andreas; Lebech, Anne‐Mette; Kronborg, Gitte
Abstract : In Denmark, patients with serious nonspecific symptoms and signs of cancer (NSSC) are referred to the diagnostic outpatient clinics (DOCs) where an accelerated cancer diagnostic program is initiated. Various immunological and inflammatory biomarkers have been associated with cancer, including soluble urokinase plasminogen activator receptor (suPAR) and the pattern recognition receptors (PRRs) pentraxin‐3, mannose‐binding lectin, ficolin‐1, ficolin‐2 and ficolin‐3. We aimed to evaluate these biomarkers and compare their diagnostic ability to classical biomarkers for diagnosing cancer in patients with NSSC. Patients were included from the DOC, Department of Infectious Diseases, Copenhagen University Hospital Hvidovre. Patients were given a final diagnosis based on the combined results from scans, blood work and physical examination. Weight loss, Charlson score and previous cancer were registered on admission, and plasma concentrations of biomarkers were measured. The primary outcome was incident cancer within 1 year. Out of 197 patients included, 39 patients (19.8%) were diagnosed with cancer. Patients with cancer were significantly older and had a higher burden of comorbidities and previous cancer diagnoses compared to patients who were not diagnosed with cancer. Previous cancer, C‐reactive protein (CRP) and suPAR were significantly associated with newly diagnosed cancer during follow‐up in multiple logistic regression analyses adjusted for age, sex and CRP. Neither any of the PRRs investigated nor self‐reported weight loss was associated with cancer. In this study, previous cancer, CRP and suPAR were significantly associated with cancer diagnosis in patients with NSSC. Ficolin‐1‐3, MBL and pentraxin‐3 were not associated with cancer. Abstract : What's new? In Denmark, patients with serious non‐specific symptoms and signs of cancer are referred to an accelerated cancer diagnostic program. But screening and diagnosis is challenging as patients form a heterogeneous group. Possible advances in the diagnostic strategy must be studied to improve accuracy and safety. This study found that the novel inflammatory biomarker suPAR and the routinely evaluated inflammatory biomarker CRP were independently associated with incident cancer diagnoses, while the innate immune markers, pentraxin‐3, mannose‐binding lectin and ficolin‐1‐3, were not. Addition of suPAR to the existing blood samples may improve diagnosis and prognostication of cancer in this heterogeneous patient group.